The Role of Impulse Buying in Mediating the Influence of Self-Reward on Financial Behavior in Generation Z - Firmansyah; Amalia Ilyas; Tri Ratnawati; Hwihanus (Escalate : Economics and Business Journal, 2026)
Generation Z grew up in a digital ecosystem that normalizes self-reward practices as a way to manage academic and work pressures, but this practice risks encouraging impulse buying that ultimately disrupts personal financial management. This study aims to analyze the role of impulse buying as a mediating variable in the relationship between self-reward and financial behavior in Generation Z. The study used a quantitative approach with a survey design of 127 Generation Z respondents aged 18–28 years selected through purposive sampling. Data were collected using a 1–5 Likert scale questionnaire that measures three variables: self-reward, impulse buying, and financial behavior, then analyzed using Structural Equation Modeling techniques based on Partial Least Squares (SEM-PLS), including evaluation of the measurement model (outer model), structural model (inner model), and mediation testing through a bootstrapping procedure of 5,000 resamples. The results showed that self-reward has a significant positive effect on impulse buying (β = 0.348; p < 0.001), and impulse buying has a significant negative effect on financial behavior (β = -0.465; p < 0.001). The direct effect of self-reward on financial behavior was insignificant after controlling for impulse buying (β = 0.122; p = 0.304), as was the total effect before the mediator was included (β = -0.040; p = 0.769), while the indirect effect proved significant (α × b = -0.162; 95% CI bootstrap bias-corrected [-0.254, -0.041]; p = 0.002). This pattern indicates full/indirect-only mediation, meaning the effect of self-reward on financial behavior in Generation Z only occurs when it operates through the impulse buying mechanism, not directly or in a zero-order manner. This study contributes to the financial behavior literature by positioning impulse buying as a crucial explanatory pathway, and offers practical implications for financial literacy education that targets consumption impulse management, rather than simply financial knowledge